Rapid identification and characterization of infected cells in blood during chronic active Epstein-Barr virus infection - Fournier, Benjamin; Boutboul, David; Bruneau, Julie; Miot, Charline; Boulanger, Cécile; Malphettes, Marion; Pellier, Isabelle; Dunogué, Bertrand; Terrier, Benjamin; Suarez, Felipe; Blanche, Stéphane; Castelle, Martin; et al. (The Journal of experimental medicine, 2020)
Epstein-Barr virus (EBV) preferentially infects epithelial cells and B lymphocytes and sometimes T and NK lymphocytes. Persistence of EBV-infected cells results in severe lymphoproliferative disorders (LPDs). Diagnosis of EBV-driven T or NK cell LPD and chronic active EBV diseases (CAEBV) is difficult, often requiring biopsies. Herein, we report a flow-FISH cytometry assay that detects cells expressing EBV-encoded small RNAs (EBERs), allowing rapid identification of EBV-infected cells among PBMCs. EBV-infected B, T, and/or NK cells were detectable in various LPD conditions. Diagnosis of CAEBV in 22 patients of Caucasian and African origins was established. All exhibited circulating EBV-infected T and/or NK cells, highlighting that CAEBV is not restricted to native American and Asian populations. Proportions of EBV-infected cells correlated with blood EBV loads. We showed that EBV-infected T cells had an effector memory activated phenotype, whereas EBV-infected B cells expressed plasma cell differentiation markers. Thus, this method achieves accurate and unambiguous diagnoses of different forms of EBV-driven LPD and represents a powerful tool to study their pathophysiological mechanisms.